The spread of rice to Japan: insights from Bayesian analysis of direct radiocarbon dates and population dynamics in East Asia - Leipe, Christian; Long, Tengwen; Wagner, Mayke; Goslar, Tomasz; Tarasov, Pavel E. (Elsevier Ltd, 2020)
The shift from foraging to agriculture as an economic way of life can be influenced by multiple ecological and cultural factors. The introduction of rice cultivation in Japan appears to have facilitated a dietary and cultural transition from the Jomon to the Yayoi cultural repertoire (10th/4th century BCE). Here we examine how rice spread across the Yayoi cultural arena (Kyushu, Shikoku, and Honshu regions) using Bayesian modelling applied to a set of radiocarbon (14C) dates obtained from carbonized rice grains. The combined results of radiocarbon analysis and archaeological data suggest that rice could have appeared in the Central Highlands already in the 11th century BCE when the region was occupied by people of the Final Jomon culture group and was mainly used for ritual purposes. It then appeared in western Japan (northern Kyushu) in the 9th century BCE and continued to disperse discontinuously across eastern Japan. This dispersal pattern likely results from the fusion of Jomon hunter–fisher–gatherer groups in eastern Japan with cultural traits introduced from the Eurasian mainland. The main driving factors for the immigration of early rice farmers into Japan (starting around 1000 BCE) appears to have been sociopolitical. Transformations in China led to the dissemination of rice farmers into the Korean Peninsula about 500 years earlier. The main drivers likely comprised: (i) the eastward expansion of the Shang dynasty (ca. 1600–1400 BCE); (ii) the eastward expansion of the Zhou kingdom, accompanied by the establishment of satellite states, such as Lu (Shandong Province) and Yan (Beijing), following the defeat of the Shang in 1045 BCE; and (iii) the strengthening of local states during the early 8th century BCE after the weakening of the Zhou, due to conflicts with agropastoralists from the Asian steppes. In addition, it is likely that the gradual middle–late Holocene decrease in summer monsoon precipitation negatively affected agricultural yields in the regions located closer to the summer monsoon boundary, such as the middle Yellow River, and thus further fostered the observed population dynamics including the spread of rice farmers to the Korean Peninsula and Japan.